VALUASI EKONOMI EROSI LAHAN PERTANIAN DI SUB DAERAH ALIRAN SUNGAI KEDUANG KABUPATEN WONOGIRI - JOKO SUTRISNO; BUNASOR SANIM; ASEP SAEFUDDIN; SANTUN R.P. SITORUS (SEPA: Jurnal Sosial Ekonomi Pertanian dan Agribisnis, 2012)
Natural resources management especially agriculture land management at Keduang Sub-Watershed will be influence of environment quality, physic (erosion, sedimentation, and debit Keduang River), chemistry (water quality) and socio economic aspect. This research aim to know the level of erosion happened in Keduang Sub-Watershed and to know the economic value of erosion in Keduang Sub-Watershed, Wonogiri Regency.